Obscenity and fabrication in equity and widening participation methodologies. (30th July 2020) - Lumb, Matt; Jane Burke, Penny; Bennett, Anna
Abstract : Equity and widening participation (EWP) initiatives in Australia are increasingly reimagined in policy as sites where participants are constructed as competitor‐individuals, with education considered only in terms of employability, social mobility and nation‐state market competition. In the context of EWP outreach, and with school students in particular, this can transpire into demands for narrow forms of 'legitimate' aspirations. Goffman defines obscenity as when (1) the very intimate is forced into the public sphere, while (2) the humanising dimensions or contexts are stripped away, with an example being pornography—where intimate encounters are reproduced as de‐contextualised acts while being made public. This article argues that dominant approaches to practicing and evaluating EWP risk obscene consequences if they force community members to present static future‐oriented valuations of intimate, fluid aspirations and experiences of education against a backdrop of increasingly individuated, competitive and standardised educational institutions. In this article, firstly we detail the context to establish a foundation for theorising consequences of particular socio‐educational discursive practices. Secondly, we engage with notions of frame, keying and fabrication as a toolbox to reveal some of the unintended (obscene) dynamics risked via certain approaches to programmatic practice and evaluation. Thirdly, we review the diversity of approaches to evaluation (and their attendant debates), highlighting the importance of these debates and diversities, making a case against methodological imperialism.